'Bastard bush': acacia thorn injuries and management. Issue 3 (10th September 2018) - Smail, Simon Johnstone; Arthur, C; Hylands, K; Stewart, C J
Abstract : This case report outlines the presentation and management of a young soldier who sustained a lower limb acacia thorn injury while on exercise in Kenya. The injury failed to heal with a subsequent ultrasound scan revealing a large retained thorn requiring surgical removal and wash out. From this case, lessons can be learnt regarding the management of thorn injuries, which are common in exercising troops in Kenya and indeed around the world. The key take-home messages are always consider a retained thorn if wounds fail to settle, use ultrasound as the imaging modality of choice, always remove identified retained thorns and if antibiotics are required use broad-spectrum antibiotics pending culture results.